PENGARUH METODE BERNYANYI TERHADAP KEMAMPUAN MENGINGAT MUFRODAT SISWA MI AL-HUDA - Fitriyah, Anis; Andreastya, Vian Hanes (PGMI UNHASY, 2025)
This study was motivated by the low ability of students to memorize Arabic mufrodat (vocabulary), which is caused by the lack of engaging and age-appropriate learning methods for elementary school students. To address this issue, the use of children's songs as a teaching method was applied as an alternative strategy to increase student interest and memory retention. This research aims to determine the effect of using the singing method on the mufrodat memorization ability of second-grade students at MI Al-Huda Banyuarang Jombang. The study employed a quantitative approach with a quasi-experimental design using a one-group pretest-posttest format. The research subjects consisted of 16 students. Data collection techniques included observation, tests, and documentation. The results showed that the average pretest score was 69.50, which increased to 76.50 in the posttest. However, the Wilcoxon statistical test showed a significance value of 0.139 > 0.05, indicating no statistically significant difference before and after applying the singing method. Nevertheless, from a practical perspective, the singing method led to improved scores and positive responses from students. This suggests that singing can be an enjoyable and effective approach to enhance Arabic vocabulary acquisition at the elementary education level.